Pengkayaan Seni, Budaya dalam Mendukung Pariwisata Berkelanjutan di Kabupaten Magelang - Muhamad, Muhamad; Santosa, Djarot Heru (STIEPAR YAPARI Bandung, 2023)
The main objective of this research is to assess the existence of diversity of cultural arts enrichment in order to become a sustainable tourism product with the criteria of protecting tourism, arts and culture of local communities in a directed and integrated manner to create something dynamic and selective. The enrichment of arts and culture in destinations has an assessment of the level of importance and level of quality based on indicators and supporting evidence that forms the criteria. The study method is carried out through qualitative descriptive analysis by revealing events or facts, circumstances, phenomena at the destination. The assessment is based on a systematic, factual description of the facts, characteristics and relationships between phenomena that occur at the destination which is measured through the level of importance and level of quality. Discussion of management at destinations with indicators in the form of a) natural sites. b) local culture, c) historical buildings d) rural landscapes, have varying levels of importance and quality. The rural landscape has a high level of importance and quality as an element of artistic and cultural enrichment in supporting quality tourism.